Peran Orang Tua Dalam Meningkatkan Motivasi Belajar Pada Anak Slow Learner - Hidayati, Beti Malia Rahma; Sasmita, Ardina; Chintya Dewi, Windy (Universitas Darul Ulum, 2023)
Parents are the main figure in the family, especially for children. The future of children also depends on the role of parents, especially in children who have special needs, in this case children with slow learner (slow learning). They need extra attention in everything, one of them in terms of learning. Providing motivation or encouragement to slow learners is an important role for parents. This study aims to determine how the role of parents in increasing learning motivation in slow learner children in SDI Al Huda 2 Full Day Program Kediri in the 2018/2019 school year. The type of research used is a qualitative approach using case studies. The research subjects were parents (guardians of students) and slow learner children at SDI Al Huda 2 Full Day Program. Data collection techniques in this study were obtained by interviews, observation, and documentation. Data obtained by researchers, analyzed by means of data reduction and conclusion. The results of the study are that the role of parents (father and mother) is a task and responsibility for their children to educate, guide, assist, provide good examples, and in the formation of character. The role of parents determines the level of motivation possessed by slow leraner children. Slow learner children need special attention and assistance in achieving learning goals. Keywords: Role of Parents, Learning Motivation, Slow Learner